The Effect Of The Project-Based Learning Model On Students’ Creative Thinking Skills In The Economics Subject - Tasyaul Hayati; Mira Chairani; Zulfikar (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the effect of the Project-Based Learning (PjBL) model on students’ creative thinking skills in economics subject. The research employed a quasi-experimental method with a non-equivalent control group design. The sample consisted of two classes: an experimental class taught using PjBL and a control class taught using conventional methods. Data were collected using a creative thinking skills test administered in both pre-test and post-test. The results showed a significant improvement in the experimental class compared to the control class. Independent sample t-test analysis confirmed that the difference was statistically significant. These findings indicate that PjBL can serve as an effective alternative learning model to improve students’ creative thinking skills, particularly in economics learning